The Role of Innate Immune Cells in Nonalcoholic Fatty Liver Disease - Marina Nati; Kyoung-Jin Chung; Triantafyllos Chavakis (Karger Publishers, 2021)
Nonalcoholic fatty liver disease (NAFLD) is a very common hepatic pathology featuring steatosis and is linked to obesity and related conditions, such as the metabolic syndrome. When hepatic steatosis is accompanied by inflammation, the disorder is defined as nonalcoholic steatohepatitis (NASH), which in turn can progress toward fibrosis development that can ultimately result in cirrhosis. Cells of innate immunity, such as neutrophils or macrophages, are central regulators of NASH-related inflammation. Recent studies utilizing new experimental technologies, such as single-cell RNA sequencing, have revealed substantial heterogeneity within the macrophage populations of the liver, suggesting distinct functions of liver-resident Kupffer cells and recruited monocyte-derived macrophages with regards to regulation of liver inflammation and progression of NASH pathogenesis. Herein, we discuss recent developments concerning the function of innate immune cell subsets in NAFLD and NASH.